2014
DOI: 10.1080/00103624.2014.956881
|View full text |Cite
|
Sign up to set email alerts
|

Extractable Silicon in Soils of the South African Sugar Industry and Relationships with Crop Uptake

Abstract: Reports of sugarcane yield responses to silicon (Si), coupled with mounting evidence that elevated crop Si levels reduce both biotic and abiotic stresses, account for the interest in theSi nutrition of this crop. In terms of managing Si supplies to sugarcane in South Africa, uncertainties exist regarding, first, the reserves of plant-available Si in soils, and second, the reliability of soil-test methods for predicting Si availability. In this study, extractable Si was measured in 112 soils collected from suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 20 publications
7
42
1
2
Order By: Relevance
“…6c), respectively. Our data corroborate the results of previous field studies (Miles et al 2014;Li et al 2018;Meunier et al 2018;Klotzbücher et al 2018;Haynes 2019), which highlight the positive relationship between pH and CaCl 2 extractable Si content after 5 or 16 h of extraction. Fourthly, the soil buffering capacity had alleviated the pH increase induced by amendments.…”
Section: Discussionsupporting
confidence: 92%
“…6c), respectively. Our data corroborate the results of previous field studies (Miles et al 2014;Li et al 2018;Meunier et al 2018;Klotzbücher et al 2018;Haynes 2019), which highlight the positive relationship between pH and CaCl 2 extractable Si content after 5 or 16 h of extraction. Fourthly, the soil buffering capacity had alleviated the pH increase induced by amendments.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the correlation between PAS indicators and soil acidity, as measured by pH, has been reported in the literature as an indicator of intensity of weathering: lower pH may be associated with low PAS in highly leached soils (Review in Haynes, 2014 andLiang et al 2015). For instance, Miles et al (2014) showed that pH and CaCl 2 -extractable Si (Si CC ) are correlated in the range of pH 3.3 to pH 7 in the South African sugarcane fields. According to the authors, such a correlation is attributable to a change in mineralogy from a less weatherable pool of Si minerals at low pH to a more weatherable pool of Si minerals at higher pH, following the conclusion of Henriet et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that CaCl 2 , which is the primary soil Si extractant used in Brazil 32 , Australia 67 and South Africa 70 , is not effective in evaluating the Si available to sugarcane regardless of the extraction method.…”
Section: Discussionmentioning
confidence: 73%